(untitled) (Journal of Surgical Sciences, 2020)
Background: Stapled Hemorrhoidopexy (SH) is a new technique with less pain than conventional hemorrhoidectomy and can be used in the management of second, third and fourth degree hemorrhoidal disease. Objective: To show the effectiveness of Stapled Hemorrhoidopexy as a treatment option of symptomatic hemorrhoid. Methods: This is an observational study. The medical records of 72 patients who had under gone Stapled Hemorrhoidopexy for symptomatic hemorrhoid disease from July 2011 to June 2013 in BIRDEM General Hospital under a same surgeon were evaluated. Data regarding postoperative pain, early and late postoperative outcome were recorded. Patient’s satisfaction assessed at 18 months follow up. Results: The study included 72 patients (50 men, 22 women) between 22 - 74 years of age (median age 39 years). The operating time was around 35 minutes. The median hospital stay was 40 hours (11- 72 hours). Early complications were fecal urgency (13.8%), urinary retention (22%), and rectal bleeding (2.77%). Late complication was pruritus ani (12.5%), thrombosis external hemorrhoids (1.38%), staple line stenosis (1.38%), recurrent hemorrhoid (2.77%), anal fissure (2.77%), and persistent mucous discharge (5.55%). The recurrence rate was 2.77% at 18 months follow up. Conclusion: Stapled hemorrhoidopexy can be safely performed with low recurrence and complication rates while offering a relatively painless postoperative period for the patient. Journal of Surgical Sciences (2017) Vol. 21 (2): 65-69